y-QUIT: Smoking Prevalence, Engagement, and Effectiveness of an Individualized Smoking Cessation Intervention in Youth With Severe Mental Illness - Curtis, Jackie; Zhang, Charry; McGuigan, Bernadette; Pavel-Wood, Esther; Morell, Rachel; Ward, Philip B.; Watkins, Andrew; Lappin, Julia (Frontiers in Psychiatry, 2018)
Introduction: Young people with psychosis are six times more likely to be tobacco smokers than their gender- and age-matched peers. Smoking is a major contributor to the 15-year reduced life expectancy among people experiencing severe mental illness (SMI). There is a lack of evidence-supported interventions for smoking cessation among young people with SMI. Material and Methods: The study comprised two phases and aimed to assess i) the prevalence of smoking among a community sample of young people with psychotic illness or at high risk of developing psychosis; ii) the proportion who engaged in the intervention; iii) the proportion who achieved smoking cessation; and iv) secondary smoking-related outcomes. In phase one, prevalence of smoking was assessed. In phase two, over a one-year period, individuals identified as smokers were invited to participate in a 12-week tailored smoking cessation intervention program that included pharmacological treatment, motivational interviewing and behavioural change techniques. Those unwilling to participate in a full intervention were offered a brief intervention. Participants of the full intervention were assessed at baseline and at week 12 endpoint on: daily cigarettes smoked (self-report), exhaled CO, nicotine dependence, readiness to quit and confidence to quit. Results: Phase one: smoking prevalence was 48.2% (53/110). Smokers were significantly more likely to be male (X2= 6.41 p=0.009). Phase two: 67.2% (41/61) eligible clients engaged in a smoking cessation intervention Effectiveness: 21 clients (34.4%) participated in a full intervention, of whom three (14.3%) received a brief intervention initially and converted to full intervention. 20 participants (32.8%) received a brief intervention only. Ten (47.6%) participants in the full intervention and five (25%) in the brief intervention dropped out. Six (28.6% of full intervention) reported smoking cessation verified by CO monitoring. Participants who completed the full intervention (n=9) reduced number of cigarettes smoked, nicotine dependence, and exhaled CO, while both readiness and confidence to quit increased. Pharmacotherapy was predominantly combination NRT (n=18; 85.7%), varenicline (4.8%), oral NRT only (4.8%) or none (4.8%). Conclusion: This pilot real-world study demonstrates that both screening for smoking and offering an effective smoking cessation intervention are achievable in youth experiencing or at risk of psychosis.